Consumer perceptions of antimicrobial use in animal husbandry: A scoping review. - Jaime R Barrett; Gabriel K Innes; Kelly A Johnson; Guillaume Lhermie; Renata Ivanek; Amelia Greiner Safi; David Lansing (PLoS ONE)
Antimicrobial use in animal agriculture is often perceived to play a role in the emerging threat of antimicrobial resistance. Increased consumer awareness of this issue places pressure on animal husbandry to adopt policies to reduce or eliminate antimicrobial use. We use a scoping review methodology to assess research on consumer perceptions of antimicrobial drugs in meat products in the United States, Canada, or the European Union. Evaluating peer-reviewed and grey literature, we included studies for assessment if they met these topical and geographic requirements, involved primary data collection, and were originally published in English. Our screening process identified 124 relevant studies. Three reviewers jointly developed a data charting form and independently charted the contents of the studies. Of the 105 studies that measured consumer concern, 77.1% found that consumers were concerned about antimicrobial use in meat production. A minority of studies (29.8% of all studies) queried why consumers hold these views. These studies found human health and animal welfare were the main reasons for concern. Antimicrobial resistance rarely registered as an explicit reason for concern. A smaller group of studies (23.3%) measured the personal characteristics of consumers that expressed concern about antimicrobials. Among these studies, the most common and consistent features of these consumers were gender, age, income, and education. Regarding the methodology used, studies tended to be dominated by either willingness-to-pay studies or Likert scale questionnaires (73.64% of all studies). We recommend consideration of qualitative research into consumer views on this topic, which may provide new perspectives that explain consumer decision-making and mentality that are lacking in the literature. In addition, more research into the difference between what consumers claim is of concern and their ultimate purchasing decisions would be especially valuable.